Entre sons e silêncios: apropriações da música no livro didático no ensino de história afro-brasileira - Luciano Magela Roza (2009)
This work has proposed research as analysis of how the music has been full of problems as a document of historical and significant educational resource potential particulary in the teaching of history afro-brazilian in this textbook. The analysis prioritizes the best of history textbooks approved and adapted by most teachers of history among those approved by PNLD 2008. In short, interested in understanding as suggested in the textbooks the use of music for teaching and learning of this issue in Brazilian education already flagged in PCNs of history, but stated in the assertion of the law 10.639/03 and related gueclelines. Considering the use of music as an educational and historical source inserted in the textbook, the practices of the suggested readings and materials of the same nature the theoretical and methodological contributions that underlie the search is linked to production around the studies of practice making and the nature of textbooks. We understand the textbook as an object of many faces and dimensions technical, educational and ideological, and its materiality, culture result of the interference of various subjects. Within the research objective are the reflection on the forms of appropriation of popular music and its uses suggested by the history textbooks and an in depth theoretical and methodological discussion on the possible interpretations of the song as an educational and historical source of possible contributions to the renewed discussion on methodologies for the teaching of history. This focusing on a first moment analysis of the appropriation of music in general and, later, more focused on episodes of the afro-brazilian history, the tax investigation is not only the studies aimed at examining the educational potential of music and, of critical and reflective way, the assumptions included in the teaching of history afro-brazilian.